2017
DOI: 10.1007/s12012-017-9429-8
|View full text |Cite
|
Sign up to set email alerts
|

Unanticipated Cardiotoxicity Associated with Targeted Anticancer Therapy in Patients with Hematologic Malignancies Patients: Natural History and Risk Factors

Abstract: Our aim is to study unanticipated cardiotoxicity associated with the use of anticancer targeted agents, a problem that remains poorly understood. Using diagnosis codes, we retrospectively identified patients with both hematologic malignancies (HM) and cardiovascular diseases (n = 820 patients). Cardiotoxicity was defined per published criteria. The targeted agents of interest included tyrosine kinase inhibitors, proteasome inhibitors, monoclonal antibodies, and immunomodulatory agents. Patients found with card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
2
10
0
1
Order By: Relevance
“…17 Clinical evidence suggests that the cardiovascular toxicity of targeted agents seems to be reversible after discontinuation of therapy. 18,19 In our study, 14 as many as 79% of patients had stable to improved LVEF on follow up. However, our study still showed that the study group had a significantly worse OS compared with the reference group, with no difference in cancer progression-free survival between the two groups.…”
Section: Natural History and Outcomesupporting
confidence: 49%
See 1 more Smart Citation
“…17 Clinical evidence suggests that the cardiovascular toxicity of targeted agents seems to be reversible after discontinuation of therapy. 18,19 In our study, 14 as many as 79% of patients had stable to improved LVEF on follow up. However, our study still showed that the study group had a significantly worse OS compared with the reference group, with no difference in cancer progression-free survival between the two groups.…”
Section: Natural History and Outcomesupporting
confidence: 49%
“…Moreover, significant uncertainty prevails in understanding the predisposing factors and the natural history of CVCs. In our retrospective study of patients, 14 who had both hematologic malignancy (multiple myeloma, leukemia, and lymphoma) and CVCs, we found that 3.5% (29 of 820) of patients experienced cardiotoxicity (study group) due to targeted agents (such as proteasome inhibitors, TKIs, anti CD20 rituximab, and immunomodulators) over the 10-year study period (2005–2014). The median time from the exposure to cardiac event was 132 days (range 1–1176 days).…”
Section: Natural History and Outcomementioning
confidence: 98%
“…It is recommended that patients receiving Carf be closely monitored for cardiac complications, however, proper monitoring strategy needs to be determined. Moreover, identifying predisposing factors for cardiotoxicity needs further research as traditional cardiovascular risk factors did not show any association in a retrospective analysis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ранние проявления кардиотоксичности возникают в течение 1 года, а поздние могут возникнуть спустя 7 лет после применения препаратов [7]. Чаще всего именно при применении антрациклиновых антибиотиков возникает нарушение фракции выброса левого желудочка [8]. Если произошло раннее выявление данного побочного эффекта, то высока вероятность того, что может произойти снижение или полное исчезновение сердечной патологии.…”
Section: антрациклиныunclassified